Facts About Iron - Linda B. Bobroff; Jennifer Hillan (EDIS)
Iron is a mineral, and it is found in every cell in the body. It’s an important part of red blood cells, which hold and carry oxygen to all of the cells. Our cells use oxygen to make energy from the food we eat. Iron also is needed to keep the immune system healthy and help brain cells work normally. This 2-page fact sheet is a minor revision written by Linda B. Bobroff and Jennifer Hillan, and published by the Department of Family, Youth and Community Sciences, November 2017.